Pengaruh Iklan, Brand Image Dan Kualitas Produk Terhadap Minat Beli Pada Produk Scarlett Di Kota Batam - Alnis Susanti Sarumaha; Tiurniari Purba (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
Competition in the business world will create many new opportunities in the business world. One form of competition in the business world is in everyday life, namely advertising for each product on several social media as well as print and electronic media where very significant progress can be seen. All companies are required to create relevant priorities in facing competition in the business world. The method used in this research is a descriptive research method, which describes and explains each objective in the influence of advertising, brand image and product quality on purchasing interest in Scarlett products. Descriptive research is research that aims to create a description with a systematic, realistic and accurate picture of the events, nature and relationships between the phenomena studied. The results obtained are Cronbach alpha values for the advertising variable, namely 0.629, brand image, namely 0.679, product quality, namely 0.760, and Buying interest is 0.665. So it was concluded that all variables had good reliability. Exact value results were obtained. Sig. (2-tailed) is 0.069 0.05 so it can be concluded that the data is normally distributed. The VIF of the advertising variable is 3,175 0.1, the VIF value of the brand image variable is 5,196 0.10 and the VIF value of product quality is 2,264 0.10. The significance value of the advertising creativity variable is 0.088 0.05. The significance value of the brand image variable is 0.98 - 0.05. The significant value of the product quality variable is 0.176 0.05. It can be concluded that advertising, Brand Image and Product Quality have a positive and significant effect on buying interest in Scarlett products in Batam City.